The Value of Memory as a Didactic Tool: “Art of Making Buildings Laboratory” at the Politecnico di Milano. (EAAE Annual Conference Proceedings, 2025)
Starting from the academic year 2022/2023, Renzo Piano has been teaching a course at the AUIC School of the Politecnico di Milano, titled “Art of Making Buildings Laboratory”.1 This course offers students a design experience grounded in the knowledge of built works, promoting a methodological approach aimed at developing the synthesis capacity that historically characterizes the architect as both a builder and an intellectual.The methodological and conceptual foundation of the course lies in the archival documents concerning the architect’s over sixty-year career, preserved by the Renzo Piano Foundation in its Genoa and Milan offices. Through the observation and analysis of graphic works and models from various phases of the design process, students are encouraged to critically reinterpret completed works.This approach aims to stimulate students to develop design proposals that address contemporary social, environmental, and economic demands.The Renzo Piano Foundation’s space at the Politecnico di Milano plays a key role in this educational experience. Sketches, plans, sections, diagrams, and models from the archive are fully available to students, becoming active tools in a design process that starts from built memory to address the needs and challenges of contemporary architecture.This contribution aims to explore the method and content of this educational experience from within, highlighting the didactic role of built works. It finds its genesis in the archival documents of the Renzo Piano Foundation, serving as a paradigm for the educational role of constructed works.1. Renzo Piano has been a professor at the ABC Department of the Politecnico di Milano since 2022, holding a direct teaching assignment as an “expert of high qualification.” The activities of the “Art of Making Buildings Laboratory”, which he leads, are supported by a group of professors from the same department, coordinated by Maria Pilar Vettori.